(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In 2025, Uzbekistan’s GDP amounted to USD 152.5 billion. This was achieved, among other factors, due to the expansion of domestic value chains, meaning that Uzbekistan has moved beyond being purely a raw-material base. Processing industries are developing at a rapid pace in the country, supported by the procurement of modern equipment. Fish production and processing are also increasing.